Irigasi dan Pendidikan Politik Etis di Kota Metro - Kurniawan, Adi; Prameswari, Anindya; Ekwandari, Yustina Sri (Universitas Negeri Surabaya, 2022)
In this study, the research focuses on the relics in the city of Metro during the application of ethical politics in the colonial era and its influence in the present. The implementation of ethical politics in Metro City has been started since 1905. By equalizing all Javanese people towards less densely populated areas, one of which is Lampung Province. In particular, Metro City, which was supported by a speech from Queen Wilhelmina, who declared a new policy to be implemented in the jurisdiction or area of application. With the existence of this new policy, namely the Application of Ethical Politics, known as the slogan of